Chronic rhinosinusitis patients have decreased lung function. Issue 10 (13th August 2014) - Kariya, Shin; Okano, Mitsuhiro; Higaki, Takaya; Noyama, Yasuyuki; Haruna, Takenori; Ishihara, Hisashi; Makino, Takuma; Onoda, Tomoo; Nishizaki, Kazunori
<x xml:space="preserve">Abstract</x> Background The relationship between upper and lower airway diseases has been reported. However, the pulmonary function of patients with chronic rhinosinusitis (CRS) has not been fully examined. Methods Pulmonary function was measured in 273 patients with CRS and 100 age‐matched normal control subjects. No patients with chronic obstructive pulmonary disease (COPD) were included in this study. The patients with CRS were divided into 8 subgroups based on the presence of asthma, sensitization to common inhaled antigens, and nasal polyposis. The relationships between pulmonary function and clinical parameters, including radiographic severity of CRS according to the Lund‐Mackay computed tomography (CT) staging system, eosinophil count in the peripheral blood, and serum total immunoglobulin E (IgE) levels, were assessed. Results In pulmonary function testing, the CRS patients had affected pulmonary function. The CRS patients without asthma showed latent obstructive pulmonary function changes when compared to normal controls. No significant correlations were observed between pulmonary function and any clinical parameters (Lund‐Mackay CT staging score, eosinophil count in the peripheral blood, and serum total IgE levels). Conclusion CRS patients had significant obstructive lung function changes regardless of the presence of asthma. The patients with CRS who had not been clinically diagnosed as having lower respiratory tract diseases might have had subclinical lower airway diseases. Therefore, clinicians should be aware of pulmonary function and lower lung diseases in patients with CRS.